Distinct Fibroblast Lineages Give Rise to NG2+ Pericyte Populations in Mouse Skin Development and Repair - Goss, Georgina; Rognoni, Emanuel; Salameti, Vasiliki; Watt, Fiona M. (Frontiers in Cell and Developmental Biology, 2021)
We have examined the developmental origins of NG2+ perivascular cell populations that adhere to the basement membrane of blood vessels, and their contribution to wound healing. Neural/glial antigen 2 (NG2) labelled most perivascular cells (70-80%) in developing and adult mouse back skin, a higher proportion than expressed by other pericyte markers TBX18, Nestin and Pdgfrβ. In adult mouse back skin NG2+ perivascular cells could be categorised into 4 populations based on whether they expressed Pdgfrα and Pdgfrβ individually or in combination, or were Pdgfr-negative. Lineage tracing demonstrated that although NG2+ cells in embryonic and neonatal back skin contributed to multiple cell types they did not give rise to interfollicular fibroblasts within the dermis. Lineage tracing of distinct fibroblast populations during skin development showed that papillary fibroblasts (Lrig1+) gave rise to NG2+ perivascular cells in the upper dermis, whilst NG2+ perivascular cells in the lower dermis were primarily derived from reticular Dlk1+ fibroblasts. Following wounding of adult skin, NG2+ dermal cells only give rise to NG2+ blood vessel associated cells and did not contribute to other fibroblast lineages. The relative abundance of NG2+ Pdgfrβ+ perivascular populations was comparable in wounded and non-wounded skin, indicating that perivascular heterogeneity was maintained during full thickness skin repair. In the wound bed NG2+ perivascular populations were primarily derived from Lrig1+ papillary or Dlk1+ reticular fibroblast lineages, according to the location of the regenerating blood vessels. We conclude that NG2+ perivascular cells represent a heterogeneous lineage restricted population that is primarily recruited from the papillary or reticular fibroblast lineages during tissue regeneration.